Age-related trends in trabecular bone scores and bone mineral density in Chinese men with type 2 diabetes mellitus: a cross-sectional study - Yunyun Lin; Juanjuan Tang; Cheng Xue; Wenjuan Di; Peng Cheng (Scientific Reports)
Abstract Patients with Type 2 diabetes mellitus(T2DM) typically have an average or higher bone mineral density (BMD) but are at a significantly higher risk of fracture than patients without diabetes. Trabecular bone score (TBS) is a textural index derived from pixel gray-level variations in lumbar spine DXA image, which has been introduced as an indirect measure of bone quality. This study aimed to discuss the trends and annual rates of change in BMD and TBS with age in Chinese men with T2DM and men without diabetes mellitus. Lumbar spine(LS) TBS was significantly lower in males with T2DM compared to men without diabetes(1.279 ± 0.117 vs. 1.299 ± 0.090, P = 0.005). However, TBS in men with T2DM peaked around age 60, which occurred later and was lower than the peak observed in men without diabetes, who reached their peak TBS around age 50 (1.294 ± 0.126 vs. 1.328 ± 0.088). Femoral neck, total hip, and lumbar spine BMD in men with T2DM were not significantly different from those in men without diabetes. The results showed that both men with or without T2DM exhibited the lowest annual rates of change in TBS at 66–75 years of age, with values of -1.05%(P < 0.001) and − 0.90%(P < 0.001), respectively. Patients with great glycemic control demonstrated higher TBS and BMD. Men with T2DM have later and lower peak TBS and faster bone loss, suggesting that diabetes may negatively impact bone microarchitecture and mineralization.